IMPLEMENTASI MODEL INKUIRI TERSTRUKTUR DALAM MENINGKATKAN PEMAHAMAN KONSEP GAYA PADA PEMBELAJARAN IPA SMP - Anggraini Ningrum, Maulidah; Ayu Permata Sari, Dhita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the improvement of students' conceptual understanding through the implementation of a structured inquiry learning model assisted by Liveworksheet on the topic of force. The low conceptual understanding of students is caused by learning activities that are still dominated by teacher explanations, resulting in limited opportunities for students to directly investigate scientific concepts. This study employed a pre-experimental method with a one-group pretest-posttest design. The subjects of this study were 31 seventh-grade students at SMP Negeri 19 Surabaya. Data collection was conducted using conceptual understanding tests in the form of pretest and posttest based on the indicators of explanation, interpretation, and application. The results showed that the application of the structured inquiry learning model assisted by Liveworksheet improved students' conceptual understanding. The improvement was indicated by the N-Gain scores on the explanation indicator of 0.87, interpretation indicator of 0.85, and application indicator of 0.78, all of which were categorized as high. These results indicate that structured inquiry learning provides students with opportunities to actively construct knowledge through investigation activities, data analysis, and drawing conclusions, so that students are able to understand and apply force concepts in different contexts.